If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -20 = 5(3x + -10) + -5x Reorder the terms: -20 = 5(-10 + 3x) + -5x -20 = (-10 * 5 + 3x * 5) + -5x -20 = (-50 + 15x) + -5x Combine like terms: 15x + -5x = 10x -20 = -50 + 10x Solving -20 = -50 + 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. -20 + -10x = -50 + 10x + -10x Combine like terms: 10x + -10x = 0 -20 + -10x = -50 + 0 -20 + -10x = -50 Add '20' to each side of the equation. -20 + 20 + -10x = -50 + 20 Combine like terms: -20 + 20 = 0 0 + -10x = -50 + 20 -10x = -50 + 20 Combine like terms: -50 + 20 = -30 -10x = -30 Divide each side by '-10'. x = 3 Simplifying x = 3
| 118=8(1+7n)-2 | | 1/5x=x | | 8(3-5a)=-296 | | 7x^(2/3)-63=0 | | 3/7b=9 | | 14+c=39 | | 22/25X15/52X8/33 | | 8(3-5a)=-188 | | 5(-3x+5)=6-4x | | 27x-19-39x=-65 | | -3(2x+3)=6x+9 | | -0.1x+1.25=-0.5x+4.45 | | 8-9t=21r-17 | | (6+y)(2y+3)=0 | | 6p-16p=70 | | 3w+2-w=-3 | | 45x-21-17x=-63 | | 84=2k-5(2k-4) | | 3(x-1)+41=x-7(x+1) | | 6(4T+1)-13=T-(T+6) | | 6x+16=-2+8x | | 24x-81+7x=19 | | 25+10(12-x)=(2x-7) | | 84=-6(6+5x) | | 18^(1/3) | | 2.5/6=h/9 | | 8/12+9k/12=7/12 | | (2m+7)-(3-4m)=0 | | 2.5p-28=2p+26 | | y=5/4x+b | | 1.75m=21 | | 7v^2+35v-42=o |